Literary Aspirations of Antanas Klementas - Stankevič, Adam (Senoji Lietuvos literatūra, 2017)
The paper deals with literary works of Antanas Klementas, which are interpreted on the basis of the facts from his biography. The data of the history of the Klementas family point to the social advancement of Antanas Klementas among his relatives: a representative of the impoverished nobility, he managed to become a member of an elite public service of a district, and later of a county. A hypothesis is suggested that his idea to publish a manuscript as a book of poems might have been be related to his wish to impart meaning to the achieved social status, and he began working on it in 1803 or 1804. In this way Klementas wanted to immortalize himself in the history of his family and to set an example to his offspring in the sense of both his career and his lifestyle. Since the poet cherished certain intellectual aspirations, he expected his works to be appreciated and disseminated. The present paper analyses pragmatic intentions of Klementas’s writing: occasional literature addressed to the people the author knew personally and ‘didactic’ texts aimed at developing the moral attitudes in his children.